2011
DOI: 10.1159/000330025
|View full text |Cite
|
Sign up to set email alerts
|

Are 25(OH)D Levels Related to the Severity of Knee Osteoarthritis and Function?

Abstract: Objective: To investigate the effect of 25-hydroxyvitamin D [25(OH)D] in Kuwaiti patients with primary knee osteoarthritis (OA) and to assess its relation with radiological grading and functional status. Subjects and Methods: In this cross-sectional study, 25(OH)D was measured using radioimmunoassay in 99 patients [90 women and 9 men; mean age 56.5 ± 9.1 years (range: 36–80)] with clinical and radiological findings of primary knee OA. X-ray grading using the Kellgren-Lawrence grading scale and the Osteoarthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 28 publications
3
15
0
1
Order By: Relevance
“…In knee OA subjects, studies investigating the association between vitamin D and physical function are scarce. Using Lequesne׳s indices to assess physical function in subjects with knee OA, Al-Jarallah et al [5] reported that serum 25(OH)D concentrations did not associate with physical function. In an intervention study, supplemental vitamin D (2000 IU/d for 2 y) increased serum 25(OH)D concentrations without improving physical function, such as standing from a chair or a 20-m walk, in subjects with knee OA [24].…”
Section: Discussionmentioning
confidence: 99%
“…In knee OA subjects, studies investigating the association between vitamin D and physical function are scarce. Using Lequesne׳s indices to assess physical function in subjects with knee OA, Al-Jarallah et al [5] reported that serum 25(OH)D concentrations did not associate with physical function. In an intervention study, supplemental vitamin D (2000 IU/d for 2 y) increased serum 25(OH)D concentrations without improving physical function, such as standing from a chair or a 20-m walk, in subjects with knee OA [24].…”
Section: Discussionmentioning
confidence: 99%
“…While some observational studies suggest a threshold of 25 hydroxyvitamin D levels above 36 ng/ml is needed for lower osteoarthritis risk (2, 7), others find no association (4, 8, 9, 10). In previously reported analyses in WHI CT participants, women with low serum 25-hydroxyvitamin D levels did have statistically significantly higher joint pain scores compared to women with higher 25-hydroxyvitamin D levels but the threshold (seen in the lowest quintile) was a much lower 12 ng/ml (6) than found in some prior studies (2, 7) .The inconsistent observational study findings (25, 26, 27) support the need for randomized clinical trials to definitively address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Both low vitamin D intake (2, 3, 4) and low 25-hydroxyvitamin D levels, (5, 6, 7) as measures of vitamin D status have been associated with increased joint pain. However, vitamin D status has been associated with knee osteoarthritis in only some (2, 5, 7) but not all (4, 8, 9, 10) observational study reports. In addition, reports from full-scale randomized trials are sparse (11).…”
mentioning
confidence: 99%
“…A significant association between serum 25-OHD deficiency and knee OA has been found [49, 50]. It has been suggested that serum 25-OHD shall be measured in any patients with symptoms suggestive of knee OA particularly at the initial stage of disease [49].…”
Section: Vitamin D and Osteoarthritismentioning
confidence: 99%
“…It has been suggested that serum 25-OHD shall be measured in any patients with symptoms suggestive of knee OA particularly at the initial stage of disease [49]. Although the level of 25(OH)D seems not to be related to the severity of the knee X-ray grading or to the functional assessment [50]. …”
Section: Vitamin D and Osteoarthritismentioning
confidence: 99%